Standardized Exchange of Clinical Documents - Gerdsen, F.; Müller, S.; Jablonski, S.; Prokosch, H.-U. (Methods of Information in Medicine, 2006)
Objectives: The exchange of medical data from research and clinical routine across institutional borders is essential to establish an integrated healthcare platform. In this project we want to realize the standardized exchange of medical data between different healthcare institutions to implement an integrated and interoperable information system supporting clinical treatment and research of glaucoma.Methods: The central point of our concept is a standardized communication model based on the Clinical Document Architecture (CDA). Further, a communication concept between different health care institutions applying the developed document model has been defined.Results: With our project we have been able to prove that standardized communication between an Electronic Medical Record (EMR), an Electronic Health Record (EHR) and the Erlanger Glaucoma Register (EGR) based on the established conceptual models, which rely on CDA rel.1 level 1 and SCIPHOX, could be implemented. The HL7-tool-based deduction of a suitable CDA rel.2 compliant schema showed significant differences when compared with the manually created schema. Finally fundamental requirements, which have to be implemented for an integrated health care platform, have been identified.Conclusions: An interoperable information system can enhance both clinical treatment and research projects. By automatically transferring screening findings from a glaucoma research project to the electronic medical record of our ophthalmology clinic, clinicians could benefit from the availability of a longitudinal patient record. The CDA as a standard for exchanging clinical documents has demonstrated its potential to enhance interoperability within a future shared care paradigm.
Keywords: Computerized medical records; integrated health care systems; glaucoma; standardization; clinical document architecture